Common Motifs in the Response of Cereal Primary Metabolism to Fungal Pathogens are not Based on Similar Transcriptional Reprogramming - Voll, Lars M.; Horst, Robin J.; Voitsik, Anna M.; Zajic, Doreen; Samans, Birgit; Pons-Kühnemann, Jörn; Doehlemann, Gunther; Münch, Steffen; Wahl, Ramon; Molitor, Alexandra; Hofmann, Jörg; Schmiedl, Alfred; et al. (Frontiers in Plant Science, 2011)
During compatible interactions with their host plants, biotrophic plant–pathogens subvert host metabolism to ensure the sustained provision of nutrient assimilates by the colonized host cells. To investigate, whether common motifs can be revealed in the response of primary carbon and nitrogen metabolism toward colonization with biotrophic fungi in cereal leaves, we have conducted a combined metabolome and transcriptome study of three quite divergent pathosystems, the barley powdery mildew fungus (Blumeria graminis f.sp. hordei), the corn smut fungus Ustilago maydis, and the maize anthracnose fungus Colletotrichum graminicola, the latter being a hemibiotroph that only exhibits an initial biotrophic phase during its establishment. Based on the analysis of 42 water-soluble metabolites, we were able to separate early biotrophic from late biotrophic interactions by hierarchical cluster analysis and principal component analysis, irrespective of the plant host. Interestingly, the corresponding transcriptome dataset could not discriminate between these stages of biotrophy, irrespective, of whether transcript data for genes of central metabolism or the entire transcriptome dataset was used. Strong differences in the transcriptional regulation of photosynthesis, glycolysis, the TCA cycle, lipid biosynthesis, and cell wall metabolism were observed between the pathosystems. However, increased contents of Gln, Asn, and glucose as well as diminished contents of PEP and 3-PGA were common to early post-penetration stages of all interactions. On the transcriptional level, genes of the TCA cycle, nucleotide energy metabolism and amino acid biosynthesis exhibited consistent trends among the compared biotrophic interactions, identifying the requirement for metabolic energy and the rearrangement of amino acid pools as common transcriptional motifs during early biotrophy. Both metabolome and transcript data were employed to generate models of leaf primary metabolism during early biotrophy for the three investigated interactions.